PENGARUH FAKTOR RISIKO AUDIT TERHADAP PENGATURAN TINGKAT MATERIALITAS DALAM PROSES AUDIT - Putri Auliya Meisha; Zahrina Ardilah; Zakiyatul A’mali Zahroh; Elvitania Sholihatun Nisa’ (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This research aims to explore the influence of audit risk factors on setting materiality levels in the financial report audit process. The research results show that audit risk has a positive and significant influence on the consideration of materiality levels in financial statement audits. Factors such as audit complexity, financial report transparency, external pressure, management commitment, materiality concept, audit compliance, and research methods also need to be considered in the audit process. In addition, the risk of material misstatement in the financial statements may be beyond the auditor's control, so the auditor needs to obtain a good understanding of the controls relevant to the audit and test internal controls manually. The risk assessment does not stop at a certain point and can be revised based on new information obtained during the audit. These findings confirm that risk has an influence on materiality settings in the financial report audit process. Therefore, a deep understanding of audit risk factors and their influence on materiality settings is very important in ensuring the success of the financial statement audit process.